I am a beautiful monster : poetry, prose, and provocation - Picabia, Francis; Lowenthal, Marc, 1969- (Cambridge, Mass. ; London : MIT Press, 2007)
The first definitive edition in English of writings by poet, painter, pickpocket-plagiarist, and consummate anti-artist Francis Picabia, one of Dada's leading figures.
Translated from the French.
boek
Keywords: Picabia, Francis